Demographic Assessment of Down Syndrome: A Systematic Review - Huete-García, Agustín (Int J Environ Res Public Health, 2021)
The objective of this study is to assess the evidence about the demographic transformation of the Down Syndrome population, with a specific focus on prenatal testing, and to identify sources frequently used for demographic assessment of Down Syndrome in the world. We reviewed existing studies on demographic transformations in the population with Down Syndrome, specifically birthrate indicators, under the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. The searches were made in Medline (via EBSCO Host), Academic Search Complete (via EBSCO Host), PsycINFO (via EBSCO Host), Web of Science (Core Collection), Public Health Database (via ProQuest), and The Cochrane Library. The terms were developed through Medical Subject Headings (MESH) and American Psycological Asociation Thesaurus of Psychological Index Terms (APA). Full texts were reviewed if information was given regarding location and birthrate for a range of three years or more, and if the first and last year considered was within 1960 and 2019. We found 22 references with a period of study between 1960 and 2019 following the global spread of prenatal testing for Down Syndrome. We found a consistent association between prenatal diagnosis and birthrate, enough to explain the significant fall in the prevalence of Down Syndrome, a somewhat rising incidence of Down Syndrome related to increased maternal age and extension of fertility services in healthcare systems, a generalized use of specific congenital birth defect registries as the primary source of data, and an unclear influence of socio-cultural and territorial variables. Our findings can inform research, policy, and practice to improve the reproductive health and quality of life of the population with Down Syndrome.